2016
DOI: 10.1248/yakushi.15-00231-2
|View full text |Cite
|
Sign up to set email alerts
|

Theory and Practice of the Constructive Jigsaw Method in Advancing Domain Knowledge and Skills in Parallel

Abstract: The Learning Sciences constitute a rapidly expanding discipline that focuses on the learning potential of humans. In this paper, I will discuss the particular learning mechanism involved in the concomitant advancement of domain knowledge and 21st century skills, as well as the Constructive Jigsaw Method of knowledge construction through collaboration-that is, collaborative problem solving. An especially important focus on knowledge construction separates routine experts from adaptive experts. While routine exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…One popular method of peer teaching is the "jigsaw" technique, in which each student specialises in a specific topic and subsequently collaborates with classmates to exchange their expertise. This technique fosters a deeper understanding of the subject matter and promotes the development of communication and teamwork skills [ 12 ]. Collaborative learning and the education reform for healthcare professionals demand that the emphasis be shifted from memorising facts to investigating, analysing, assimilating, and synthesising knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…One popular method of peer teaching is the "jigsaw" technique, in which each student specialises in a specific topic and subsequently collaborates with classmates to exchange their expertise. This technique fosters a deeper understanding of the subject matter and promotes the development of communication and teamwork skills [ 12 ]. Collaborative learning and the education reform for healthcare professionals demand that the emphasis be shifted from memorising facts to investigating, analysing, assimilating, and synthesising knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…In Iran, research has shown that the jigsaw collaborative approach has positive impacts on and improves self-concept and motivation of elementary school students (25). Fortunately, the collaborative jigsaw approach makes the members of a group gain a deeper understanding of science and helps them perceive a better mastery over a concept and create new knowledge (26). By applying the jigsaw approach, students, especially freshman university students, can develop an effective technique to deal with integrated subjects (15).…”
Section: Discussionmentioning
confidence: 99%